Cambodia : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Cambodia's Poverty Reduction Strategy Paper Progress. The Cambodian economy grew by 5.2 percent in 2003 compared with 5.5 percent in 2002, led by continued growth in garments exports, a rebound in overall investments and an upward surge in agricultural production. The drop in foreign direct investment has been more than compensated by domestic private investment and higher consumption induced by higher public spending. Moreover, the weakness in the service sector receipts has been offset by continued strong growth in garments exports.